Migration, Post-Socialism, and Diasporic Experiences. Fragmented Lives, Entangled Worlds / Migration, Postsozialismus und Diaspora-Erfahrungen. Fragmentierte Leben, verflochtene Welten - Jasina-Schäfer, Alina; Aivazishvili-Gehne, Nino (Journal für Kultur und Geschichte der Deutschen im östlichen Europa (JKGE) / Journal for Culture and History of the Germans in Eastern Europe, 2024)
This issue aims to deepen our understanding of the mobility and complex diasporic experiences of individuals from the former Soviet Union, exploring their intricate histories, current circumstances, and future aspirations. It focuses on the relationship between concepts such as "diaspora" and "(post-)socialism", highlighting migration as a phenomenon that not only unites these analytical frameworks but also necessitates their re-evaluation.